The girl by the bridge - Arnaldur Indriðason, 1961- (Arnaldur Indriðason, 1961- Detective Konrad novel., 2023)
"An elderly couple are worried about their granddaughter. They know she's been smuggling drugs, and now she's gone missing. Looking for help, they turn to Konrad, a former policeman whose reputation precedes him. Always absent-minded, he constantly ruminates on the fate of his father, who was stabbed to death decades ago. But digging into the past reveals much more than anyone set out to discover, and a little girl who drowned in the Reykjavik city pond unexpectedly captures everyone's attention. A brilliant, chilling tale of broken dreams and children who have nowhere to turn"--